2015
DOI: 10.1002/ajhb.22771
|View full text |Cite
|
Sign up to set email alerts
|

The association between economic development, lifestyle differentiation, and C‐reactive protein concentration within rural communities in Hainan Island, China

Abstract: Given that CRP concentration is a marker of future CVD risk, this study suggests that within these previously homogenous rural communities, economic development might have stratified people into population subgroups with a different CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In a study undertaken in England [ 47 ], multiple aspects of the residential environment (e.g., trust, integration into the wider society, a left-wing political climate, the physical quality of the residential environment, and the unemployment rate) had a larger effect for females than males in terms of self-rated health. Inoue et al [ 52 ] also found that females were more affected by neighborhood socioeconomic characteristics (i.e., differences in the Gini coefficient) than men in terms of C-reactive protein concentration in rural China. Furthermore, while studying the French population, Vallée et al [ 53 ] suggested that females might be more influenced by the place where they live since they tend to spend more time in their community surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…In a study undertaken in England [ 47 ], multiple aspects of the residential environment (e.g., trust, integration into the wider society, a left-wing political climate, the physical quality of the residential environment, and the unemployment rate) had a larger effect for females than males in terms of self-rated health. Inoue et al [ 52 ] also found that females were more affected by neighborhood socioeconomic characteristics (i.e., differences in the Gini coefficient) than men in terms of C-reactive protein concentration in rural China. Furthermore, while studying the French population, Vallée et al [ 53 ] suggested that females might be more influenced by the place where they live since they tend to spend more time in their community surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration of high‐sensitivity CRP (hs‐CRP) is a marker of chronic and low‐grade inflammation linked to elevated risk of CVDs (Ridker, 2003). Additionally, it has been reported that the variation in hs‐CRP is influenced by various factors, such as age and lifestyle (Inoue et al, 2016; McDade et al, 2011).…”
Section: Introductionmentioning
confidence: 99%